«Lenin knew how to dream»: Temporal sequence and narrative landscapes of memory of the Soviet past - F. V. Nikolai (Шаги)
A review of: Veselkova, N. V., Gramatchikova, N. B., Enina, L. V., & Priamikova E. V. (2022). Mechty i pamiat’: narrativnye landshafty nebol’shogo sovetskogo goroda [Dreams and memories: narrative landscapes of a small Soviet city]. Kabinetnyi uchenyi. (In Russian).